Comparative study of the effect of gamma-radiation on the structural and thermophysical properties of nitrile-butadiene rubber filled with different nanometal oxides - Khankishiyeva, R.F.; Mammadov, S.M.; Akhundzada, H.N.; Mammadov, J.S.; Azadaliyev, A.I.; Ismayilova, P.I.; Mammadova, G.A. (Вопросы атомной науки и техники, 2020)
In the present work, the structure and thermal properties of nanocomposites based on nanometal oxides (ZnO, Al₂O₃, ZrO₂) and aromatic disulphochloride benzene compounds in a butadiene nitrile rubber (NBR) matrix that are obtained by gamma-rays processing have been investigated. Structural changes of nanocomposites depend on the type of used nanoparticles which have been identified by Fourier Transform Infrared (FTIR) spectroscopy and Electron Paramagnetic Resonance (EPR). Analysis by Scanning Electron Microscope (SEM) was used to study the morphology phase of the nanoparticles in the polymer matrix and the interface between the polymer-filler. In addition, the results of the samples based on NBR were obtained by thermogravimetric analysis (TGA)/differential thermal analysis (DTA). The results show that, the thermal stability of nanocomposites significantly decreased after irradiation, but with the addition of a certain amount of benzene-1,3-disulfonyl chloride (DSChB) and nanometal oxides to rubber blend the thermal stability could be improved.